Analisis Perbedaan Kebijakan Standar Perizinan Reklamasi Pada Wilayah Pelabuhan dan Selain Pelabuhan - Gultom, Iqbal Suhaemi; T.Danny, Anggoro; Pramono , Hadi (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2023)
Reclamation is a business activity that is categorized as a high-risk level. Currently, Indonesia has 2 (two) standards for implementing coastal reclamation that is set by the Ministry of Marine Affairs and Fisheries (KKP) and the Ministry of Transportation (Kemhub). KKP sets reclamation standards outside the port area based on Law Number 27 of 2007 (UU Number 27 of 2007) and the Ministry of Transportation determines reclamation standards in port areas based on Law Number 17 of 2008 (UU Number 17 of 2008). This study uses a qualitative method through a literature review to compare the two reclamation standards which can help simplify business permits according to Perppu Number 2 of 2022. Based on a comparison of the reclamation standards used by the KKP it can be applied to all area inside and outside the port because it regulates standards in more detail thereby reducing potential impacts of reclamation that may occur.